Dual antiplatelet therapy (PEGASUS) vs. dual pathway (COMPASS): a head-to-head in vitro comparison. (17th February 2022) - Clifford, Cole R.; Jung, Richard G.; Hibbert, Benjamin; Chong, Aun Yeong; Lordkipanidzé, Marie; Tanguay, Jean-Francois; So, Derek Y.F.
Abstract: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 inhibitor is prescribed for 1-year after myocardial infarction. Two clinical strategies are considered at 1-year: continuation of DAPT or "Dual Pathway" (DP), using aspirin and rivaroxaban. No head-to-head comparative studies exist. In our in-vitro study, 24 samples of donor blood were treated with clinically proven concentrations of 5 antithrombotic regimens: aspirin, ticagrelor, rivaroxaban, DAPT, and DP. Thrombosis was analyzed using the Total Thrombus Analysis System (T-TAS) to measure both antiplatelet and anticoagulant effects. Flow cytometry was performed to quantify platelet activation. DAPT was the most potent antiplatelet regimen, delaying thrombus onset ( p < .0001) and reducing thrombogenicity ( p < .0001), relative to control. DP did not delay thrombus formation relative to aspirin alone ( p = .69). DP was the most potent anticoagulant regimen, delaying thrombus onset ( p < .0001) and reducing thrombogenicity ( p < .0001), relative to control. DP showed synergistic antithrombotic effects by delaying thrombus onset ( p < .0001) and reducing thrombogenicity ( p = .0003), relative to rivaroxaban alone. Flow cytometry showed only DAPT ( p = .0023) reduced platelet activation. DP treatment demonstrated synergistic antithrombotic effects over rivaroxaban alone, but no additional antiplatelet synergism over aspirin alone.